The general solution of the differential equation will be in the form:
"y=y_1(x)+y_2(x)" Since the solutions are linearly independent, we assume
"y_2(x) = y_1(x)v(x) \\implies y_2=vx^2\\qquad \\cdots (1)" Hence,
"y_2'(x) = 2vx +v'x^2 \\qquad\\cdots (2)\\\\\ny_2''(x) = 2v+4xv'+x^2v'' \\quad \\cdots (3)" Substitute (2) and (3) in (1):
"x^2(2v+4xv'+x^2v'')-3x(2vx+v'x^2)+4vx^2=0"
Simplifying the above:
"2vx^2+4x^3v'+x^4v''-6vx^2-3v'x^3+4vx^2=0\\\\\nx^4v''+x^3v'=0\\\\" Thus:
"xv''+v'=0 \\qquad \\cdots (4)" Let:
"w=v' \\qquad\\cdots (5)\\\\\nw'=v'' \\qquad\\cdots (6)" Put (5) and (6) in (4)
"xw'+w=0\\\\\nxw'=-w\\\\\n-\\frac{w'}{w}=\\frac{1}{x}" Integrate both sides
"\\int-\\frac{w'}{w}dw=\\int \\frac{1}{x}dx\\\\\n-\\ln w =\\ln x\\\\\n\\ln w^{-1} = \\ln x\\\\\nw^{-1} = x \\implies w=\\frac{1}{x}" Recall:
"v'(x)=w \\implies v=\\int w dx = \\int \\frac{1}{x}dx = \\ln x" Hence
"v= \\ln x \\qquad \\cdots (7)" Put (7) in (1), we get:
"y_2 = x^2 \\ln x" Which is the second solution.
The general solution is therefore:
"y=C_1x^2+C_2x^2 \\ln x"
Comments
Leave a comment